2018
DOI: 10.1002/ar.23740
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Hindlimb Membrane Musculature of Bats: Implications for Active Control of the Calcar

Abstract: The striking postcranial anatomy of bats reflects their specialized ecology; they are the only mammals capable of powered flight. Bat postcranial adaptations include a series of membranes that connect highly-modified, or even novel, skeletal elements. While most studies of bat postcranial anatomy have focused on their wings, bat hindlimbs also contain many derived and functionally important, yet less studied, features. In this study, we investigate variation in the membrane and limb musculature associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Functionally diverse calcars should exhibit anatomical divergence based on differing functional requirements. For instance, in Myotis, long calcars were found to be associated with a trawling foraging strategy (Fenton and Bogdanowicz 2002), and muscles associated with the calcar were found to vary anatomically in three species with different flight and foraging strategies (Stanchak and Santana 2018).…”
Section: Pteromyine Rodents (~50 Species)mentioning
confidence: 99%
“…Functionally diverse calcars should exhibit anatomical divergence based on differing functional requirements. For instance, in Myotis, long calcars were found to be associated with a trawling foraging strategy (Fenton and Bogdanowicz 2002), and muscles associated with the calcar were found to vary anatomically in three species with different flight and foraging strategies (Stanchak and Santana 2018).…”
Section: Pteromyine Rodents (~50 Species)mentioning
confidence: 99%
“…The morphological comparison of the hindlimbs of adults of N. leporinus , N. albiventris (data from this study), D. rotundus , M. molossus and A. lituratus (Reyes‐Amaya et al, ), exhibits that N. leporinus and N. albiventris share the same bone elements and bone morphology (Figure b), revealing a set of six (6) characters shared by the noctilionid fisher bats (Noctilionidae), absent in the previously examined species (Table ): The calcar basal crest (a highly developed biconcave keel that extends along the proximal portion of the lateral surface of the calcar; Figure c), which constitutes an increase in the origin surface for the m. calcaneocutaneus (adductor muscle) and the insertion surface for the m. depressor ossis styliformis (abductor muscle, Schutt & Simmons, ; Stanchak & Santana, ). It has been reported that the calcar bone in bats serves as structural support for the edges of the uropatagium, facilitating the use of the uropatagium as a sac to capture and/or handle the food and as a rudder in manoeuvrability during flight (Schutt & Simmons, ; Stanchak & Santana, ; Vaughan, ).…”
Section: Discussionmentioning
confidence: 63%
“…The morphological comparison of the hindlimbs of adults of N. leporinus , N. albiventris (data from this study), D. rotundus , M. molossus and A. lituratus (Reyes‐Amaya et al, ), exhibits that N. leporinus and N. albiventris share the same bone elements and bone morphology (Figure b), revealing a set of six (6) characters shared by the noctilionid fisher bats (Noctilionidae), absent in the previously examined species (Table ): The calcar basal crest (a highly developed biconcave keel that extends along the proximal portion of the lateral surface of the calcar; Figure c), which constitutes an increase in the origin surface for the m. calcaneocutaneus (adductor muscle) and the insertion surface for the m. depressor ossis styliformis (abductor muscle, Schutt & Simmons, ; Stanchak & Santana, ). It has been reported that the calcar bone in bats serves as structural support for the edges of the uropatagium, facilitating the use of the uropatagium as a sac to capture and/or handle the food and as a rudder in manoeuvrability during flight (Schutt & Simmons, ; Stanchak & Santana, ; Vaughan, ). The presence of the calcar basal crest (Tables and ) at N. leporinus and N. albiventris suggests the high importance of the uropatagium–calcar complex (and associated muscles) in noctilionid fisher bats, related to the need to contract the uropatagium during the acquisition of the prey (avoiding the friction with the water, Vaughan, ) and its posterior use to handle the food (Bordignon, ; Brooke, ). The tibial lateral crest (extending along the lateral surface of the tibia, from one‐third way of the diaphysis length to its distal end; Figure c), which constitutes an increase in the origin/insertion surface for the m. extensor hallucis longus (rotation of the autopodium craniad and dorsad), m. gracilis (flexion of the shank and adduction of the hindlimb), m. semitendinosus and m. semimembranosus (extension of the femur and flexion of the shank, Vaughan, ).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations